Synthetic routes towards pyrimido[1,2-a][1,3,5]triazines (Review) - Dolzhenko, Anton (The Japan Institute of Heterocyclic Chemistry, 2011)
The present review summarizes information on the synthetic approaches to compounds with pyrimido[1,2-a][1,3,5]triazines, 1,3,5-triazino[2,1-b]quinazolines (benzofused pyrimido[1,2-a][1,3,5]triazines), and other polyfused heterocyclic systems bearing these scaffolds. Data concerning potential applications of the pyrimido[1,2-a][1,3,5]triazines, particularly as biologically active agents, are also discussed.